Multicenter matched-pair analysis of extended right lobe versus whole organ liver transplantation: a snap shot of the tragic situation in Germany - Herden, Uta; Nadalin, Silvio; Scherer, Marcus N.; Mehrabi, Arianeb; Braun, Felix; Paul, Andreas; Gül-Klein, Safak; Pratschke, Johann; Fischer, Lutz (Transplantation)
An abstract is unavailable.
Gesehen am 10.11.2022